SERUM IGM AND IGG TITERS 2 WEEKS AND 8 WEEKS FROM BEGINNING OF SYMPTOMS AND THEIR RELATION TO SEVERITY IN COVID-19 - Amin, Sabir Mohamed; Al-Shaikhani, Mohamed Abdulrahman; Abdulrahman, Rebwar Faraj (Journal of Sulaimani Medical College, 2025)
Background COVID-19 pandemic, which started in late December 2019, has resulted in a significant number of morbidity and mortality worldwide. Estimating serum antibody titers of both IgM & IgG against the coronavirus in patients plays a crucial role in diagnosis and assessing the severity of the infection. Objectives Our objective is to assess IgM and IgG levels at 2 and 8 weeks from the onset of COVID-19 symptoms and examine their relationship with disease severity and mortality. Additionally, we aim to determine how these antibody levels relate to patient age, BMI, gender, and any chronic illnesses they may have. Patients and Methods This prospective study was conducted at Dr. Hemn Teaching Hospital in Sulaymaniyah, from December 4th, 2021 to March 5th, 2022. It included 33 males and 28 females, aged between 17 and 92 years, all of whom were confirmed to have COVID-19 by Reverse Transcription Polymerase Chain Reaction and/or High-resolution computed tomography. Blood samples were taken 2 and 8 weeks from starting symptoms and processed by ELISA to detect IgM and IgG titers. Results Male patients accounted for 54.1%, and 63.93% were between 30-70 years of age, with 90.16% residing in the city center. The majority were non-smokers (68.85%), and 86.89% did not consume alcohol. In terms of infection severity, 22.95% had mild cases, 40.98% were moderate and 36.07% were severe-critical infections. We observed that higher antibody titers in the early phase were associated with increasing severity and mortality. A higher body mass index was identified as a risk factor for elevated antibody production while hypertension and diabetes were not. Conclusion Our findings suggest that higher levels of IgM and IgG antibodies during the early phase of COVID-19 are associated with increased disease severity and, consequently, higher mortality rates. Furthermore, a higher BMI was found to be a risk factor for elevated antibody production. After 8 weeks from symptoms, IgG levels remained elevated, while IgM levels declined sharply.
Keywords: COVID19 coronavirus disease of 2019; ELISA; RTPCR